Vibration Performance Assessment of a Long-Span Concrete Floor Using Field Measurements over a Five-Year Period. Issue 8 (August 2014) - Chen, Jun; Yan, Shixin; Zhang, Mengshi
Field tests were conducted on a unique long-span post-tensioned concrete floor between 2008 and 2013. The measurements cover the important construction stages including completion of the structural floor, installation of the false floor, completion of the whole building and opening the building to the public. This paper assesses the vibration performance of the floor using field measurements. Natural frequencies, damping ratios, mode shapes and modal masses of the floor were identified from ambient vibration measurements for eight different stages. A clear decreasing trend of the natural frequencies has been observed since 2009 when the building was opened to the public. Moreover, the natural frequencies decrease while the damping ratio increases with increasing vibration amplitude. It is found that, in this case, the false floor provides no contribution to the stiffness or the damping of the structural floor. Peak responses of the floor under controlled excitation, such as a single person walking and a group of people walking, are compared. Peak responses of the floor under operational excitation are presented, including the annual maximum response for four continuous years and the maximum responses for different numbers of occupants.